Respuesta :

Answer:

[tex]f(x)+g(x)=-x+4[/tex]

Step-by-step explanation:

We have the functions, [tex]f(x)=3x-2[/tex] and [tex]g(x)=6-4x[/tex].

It is required to find the sum of these functions.

That is, [tex]f(x)+g(x)[/tex].

On substituting the functions, we get,

[tex]f(x)+g(x)=(3x-2)+(6-4x)[/tex]

i.e. [tex]f(x)+g(x)=(3x-4x)+(6-2)[/tex]

i.e. [tex]f(x)+g(x)=-x+4[/tex]

Thus, the sum of the functions i.e. [tex]f(x)+g(x)=-x+4[/tex].

Answer:

-x+4 is the answer.

Step-by-step explanation:

We have given two functions.

f(x) = 3x-2

g(x) = 6-4x

We have to find the addition of given two functions.

f(x)+g(x) = ?

Putting given values in above equation, we have

f(x)+g(x) = (3x-2)+(6-4x)

f(x)+g(x) = 3x-2+6-4x

adding like terms ,we have

f(x)+g(x) = (3-4)x+(6-2)

f(x)+g(x) = (-1)x + (4)

f(x)+g(x) = -x +4 which is the answer.